Effect of Rosemary on Stabilization of Proteins during Frozen Storage of Mackerel (Scomber scombrus). Issue 2 (7th February 2021) - Kvangarsnes, Kristine; Rustad, Turid; Barnung, Trygg; Emblem Larssen, Wenche; Aas, Grete Hansen
ABSTRACT: The effect of rosemary extract ( Rosmarinus officinalis L ) as an antioxidant on the quality of Atlantic mackerel ( Scomber scombrus ) fillets stored at −30°C for nine months was studied. Results showed that immersion in rosemary extract prior to frozen storage decreased the oxidative reactions in lipids and peroxide value (PV) and thiobarbituric acid (TBARS) as well as in proteins. For proteins, the most distinct changes were observed in the myofibrillar proteins, and carbonyls were found to be the most affected parameter. Formation of carbonyls increased significantly in fillets without rosemary extract, while carbonyl content in fillets immersed in rosemary extract remained stable.